2010
DOI: 10.1021/ja105389t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structural Changes at LiMn2O4/Electrolyte Interface during Lithium Battery Reaction

Abstract: Gaining a thorough understanding of the reactions on the electrode surfaces of lithium batteries is critical for designing new electrode materials suitable for high-power, long-life operation. A technique for directly observing surface structural changes has been developed that employs an epitaxial LiMn(2)O(4) thin-film model electrode and surface X-ray diffraction (SXRD). Epitaxial LiMn(2)O(4) thin films with restricted lattice planes (111) and (110) are grown on SrTiO(3) substrates by pulsed laser deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
368
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(384 citation statements)
references
References 44 publications
10
368
1
2
Order By: Relevance
“…6), suggesting gradual SEI growth during cycling. The SEI thickness obtained in this study by indentation was thicker than the reported values measured by other techniques, such as ellipsometry and TEM, 9,11,22 which reported that the SEI thickness was in the range of 2-5 nm, much smaller than the result in this study. The relatively thin SEI from TEM measurements probably appears because of SEI decomposition by the focused electron beam under high vacuum condition, 10 while the ellipsometry technique seems to underestimate the thickness due to an assumption of an optically homogeneous and isotropic SEI.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…6), suggesting gradual SEI growth during cycling. The SEI thickness obtained in this study by indentation was thicker than the reported values measured by other techniques, such as ellipsometry and TEM, 9,11,22 which reported that the SEI thickness was in the range of 2-5 nm, much smaller than the result in this study. The relatively thin SEI from TEM measurements probably appears because of SEI decomposition by the focused electron beam under high vacuum condition, 10 while the ellipsometry technique seems to underestimate the thickness due to an assumption of an optically homogeneous and isotropic SEI.…”
contrasting
confidence: 85%
“…It has been known that thin surface layer can be formed on electrode surface by contact with electrolyte. 11,12,22 The growth of the SEI during the initial cycle is rapid (1.526 nm/cycle), suggesting that the low Coulombic efficiency during the initial cycling test can be attributed to rapid SEI growth on the LiMn 2 O 4 surface. This is consistent with the studies that correlated SEI formation with Coulombic efficiency.…”
mentioning
confidence: 99%
“…Hirayama et al and Liu et al found, that the {110} facets are vulnerable to manganese dissolution. 28,33,34 Since the cycling of 2 Li eq. involves Mn 4+ /Mn 3+ as the active redox couple below 3.5 V vs. Li + /Li, there is a higher risk of manganese disproportionation and dissolution during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…The wavelength of X-ray used was 0.82552 ¡ (15 keV), and the detailed measurement conditions were described elsewhere. 14,18 In the XRD measurements, a reciprocal coordinate system (H,K,L) tetra was used when L describes the projection along the surface normal direction while H and K indicate the projection parallel to the surface. The reciprocal coordinate system was a tetrahedral system, and the relation between (H,K,L) tetra and (h,k,l) cubic is as follows: for two diffraction peaks; the out-of-plane (0,0,8) tetra and in-plane (4,0) tetra diffraction peaks, which correspond respectively to the (440) cubic and (004) cubic reflections for the original cubic cell.…”
Section: ¹3mentioning
confidence: 99%